Effects of different live prey enhancement on the expression of selected immune and appetite related genes during early development of cod (Gadus morhua L) larvae - Leifur Guðni Grétarsson 1990- (2014)
Í samráði við leiðbeinanda og umsjónarmann lokaverkefna við Auðlindadeild Háskólans á Akureyri er lokaverkefni nemanda til B.S. gráðu í líftækni í formi vísindagreinar sem send hefur verið viðurkenndu fræðiriti til birtingar. Efnið er því skrifað á enskri tungu og í þeirri uppsetningu sem fræðiritið gerir kröfu um. Þessu til vitnis fylgir staðfesting á innsendingu greinarinnar. High mortalities in early stages of Atlantic cod (Gadus morhua L) larvae produced in intensive aquaculture are commonly experienced and have been linked to mainly feeding and nutrition. The immune system of cod larvae is poorly developed at hatch, and innate immune parameters therefore of importance for defence against environmental microorganism. Also higher quality larvae result in improved development during later stages. In the present study, the live prey of cod larvae was additionally enhanced using a fish protein hydrolysate or marine microalgae and offered to larvae in different treatment schedules. The results indicate that the enhancement affected the expression levels of appetite and immune related genes. The observed reduction in total lipid content and DHA:EPA ratio in live prey enhanced with marine microalgae is of concern, however, there are strong indications of improved larval survival in this group and improved growth of larvae in all groups offered additionally enhanced live prey. Also, the increased gene expression observed may result in improved disease resistance, growth and overall performance during later stages. The enhancement resulted in different mineral content of the diets, but their role in growth, development and gene expression is not fully known. Léleg afkom lirfa Atlantshafs þorsks (Gadus morhua L) er þekkt vandamál í fiskeldi og hefur aðallega verið tengd fóðrun og fæðu. Ónæmiskerfi þorsklirfa er óþroskað við klak og því er ósérhæfð ónæmissvörun mikilvæg vörn gegn örverum úr umhverfinu. Einnig hafa aukin gæði þorsklirfa skilað sér í betri vexti á seinni þroskastigum. Í þessari rannsókn voru fæðudýr ...